Production Methods of Ready-to-Use Fermented Vinegar Starter Culture - Treesuwan, Khemmapas; Yodin , Kanokwan; Kanyakum, Kanyarat (Rajamangala University of Technology Tawan-ok Research Journal, 2024)
Fermented vinegars are popular as healthy drinks due to their high nutritional value and ability to balance the various systems in the body. For example, reduces blood pressure, decreases the risk of cardiovascular disease, prevents infection and antivirus. However, the fermentation processes are complicated, and the procedures can take place only in the laboratories. Therefore, this study aimed to develop a ready-to-use vinegar starter culture for vinegar fermentation and convenient transportation. In this study was conducted to develop dry starter culture for vinegar fermentation to facilitate production, transportation, and reduce microbial contamination. Raw materials were compared to the suitability of four substrates (rice flour, pineapple pulp, rice bran, and rice bran) for starter culture production. The additives that could reduce contamination in the production of dry starter culture for vinegar fermentation were also investigated. Moreover, the study investigated the optimum temperature and storage period for starter culture that could affect the efficiency of vinegar fermentation. Acetobacter aceti TISTR 354 was used in a semi-continuous fermentation process. The results showed that rice bran mixed with 95% ethanol and 0.2% propionic acid stored at 4 °C could reduce contamination and be stored for up to 5 weeks. From week 1 to 5, the average acetic acid production was 6.08% and 4.50%, respectively, which were significantly different (p < 0.05).